IMPLEMENTASI SISTEM INFORMASI POIN REWARD MEDIA SOSIAL CV KINAYA JAYA BERBASIS CODEIGNITER 3: IMPLEMENTASI SISTEM INFORMASI POIN REWARD MEDIA SOSIAL CV KINAYA JAYA BERBASIS CODEIGNITER 3 - Jamallulail, Muhammad Hasan; Wendy Asswan Cahyadi; Suhendra Anjar Dinata (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
This study applies web-based Information System technology for calculating reward points on social media posts at CV Kinaya Jaya Keke Busana. The research method used is Research and Development, while the system development applies the Waterfall approach. The system is built with PHP 7.4.3 and the CodeIgniter 3 framework to facilitate the management of reward point calculations and daily operational integration. The results of functional testing using Black Box on 12 main components show that all scenarios run well without bugs or validation failures. The feasibility of the system is tested with User Acceptance Testing based on ISO/IEC 25010 which produces a high average score on four main dimensions, namely Functionality 87.90 percent, Reliability 85.52 percent, Usability 87.62 percent, and Efficiency 89.33 percent. The construct validity test meets the requirements of r count greater than r table 0.433 and p less than 0.05, while the reliability of the instrument produces Cronbach's Alpha 0.816 for Functionality and 0.823 for Reliability. These findings confirm that the system is effective, reliable, and user-acceptable for reward point management needs in a corporate environment.